2018
DOI: 10.1073/pnas.1719902115
|View full text |Cite
|
Sign up to set email alerts
|

Bryostatin-1 alleviates experimental multiple sclerosis

Abstract: Multiple sclerosis (MS) is an inflammatory disorder targeting the central nervous system (CNS). The relapsing-remitting phase of MS is largely driven by peripheral activation of autoreactive T-helper (Th) 1 and Th17 lymphocytes. In contrast, compartmentalized inflammation within the CNS, including diffuse activation of innate myeloid cells, characterizes the progressive phase of MS, the most debilitating phase that currently lacks satisfactory treatments. Recently, bryostatin-1 (bryo-1), a naturally occurring,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
64
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(66 citation statements)
references
References 26 publications
0
64
0
2
Order By: Relevance
“…Multiple sclerosis (MS) is an inflammation of the CNS, mainly driven by self-activated T-helper (Th) 1a nd peripheral activation of Th17 lymphocytes, while diffuse activation of myeloid cells is ap rogression of MS and currently has no satisfactory treatment. In 2018, the researchers at the John Hopkins University brought the hope for the treatment of MS, they discovered that bryo 1 could preventthe progresso fM S. [41] 2.5 Inhibitory activity of bryostatin 1o nc ell aging Fibroblasts are responsible for the synthesis of structural proteins (e.g.,c ollagen) that support the structural integrity of the skin andp romote wound healing. Bryo 1 facilitated the activation and survival of human dermal fibroblasts under stressful conditions and promoted rejuvenationo fh ealthy skin.…”
Section: Bioactivitiesofb Ryostatin 1i Ncentral Nervous System Diseasesmentioning
confidence: 99%
“…Multiple sclerosis (MS) is an inflammation of the CNS, mainly driven by self-activated T-helper (Th) 1a nd peripheral activation of Th17 lymphocytes, while diffuse activation of myeloid cells is ap rogression of MS and currently has no satisfactory treatment. In 2018, the researchers at the John Hopkins University brought the hope for the treatment of MS, they discovered that bryo 1 could preventthe progresso fM S. [41] 2.5 Inhibitory activity of bryostatin 1o nc ell aging Fibroblasts are responsible for the synthesis of structural proteins (e.g.,c ollagen) that support the structural integrity of the skin andp romote wound healing. Bryo 1 facilitated the activation and survival of human dermal fibroblasts under stressful conditions and promoted rejuvenationo fh ealthy skin.…”
Section: Bioactivitiesofb Ryostatin 1i Ncentral Nervous System Diseasesmentioning
confidence: 99%
“…We previously reported that naturally-derived bryo-1 inhibits production of pro-inflammatory cytokines (such as IL-12) by lipopolysaccharide (LPS)-stimulated murine bone marrow-derived dendritic cells (mBMDCs), while augmenting production of regulatory cytokines such as IL-10 ( Kornberg et al, 2018). These actions were associated with the beneficial effects of bryo-1 we observed in autoimmune neuroinflammation.…”
Section: Identification Of Synthetically Designed Pkc Modulators Thatmentioning
confidence: 73%
“…We recently reported that natural bryo-1 attenuates neuroinflammation in a mouse model of MS by specifically targeting myeloid cells of the innate immune system, skewing the phenotype of macrophages and DCs from pro-inflammatory to anti-inflammatory/reparative phenotypes (Kornberg et al, 2018). Whether PKC isoforms are the key molecular targets mediating these immunologic actions has remained under investigation, as bryo-1 has also been reported to act directly on toll-like receptor 4 (TLR4) to activate myeloid differentiation primary response 88 (MyD88)-independent signaling through TIR-domain-containing adapter-inducing interferon- (TRIF) (Ariza et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The final concentration of Bry‐1 was 10 μg/mL. The treatment group received an intraperitoneal (ip) injection of 30 μg/kg Bry‐1 every other day for 4 weeks, and the control groups received an equal volume of vehicle control (20% ethanol and 1% DMSO in PBS) every other day for 4 weeks, as previously described . After 4 weeks, the mice were killed under anaesthesia.…”
Section: Methodsmentioning
confidence: 99%